Assessing Cardiovascular Knowledge Gaps in Iraq Nursing Students: Menilai Kesenjangan Pengetahuan Kardiovaskular pada Mahasiswa Keperawatan Irak - Khadija Mohammed Jassim (Universitas Muhammadiyah Sidoarjo, 2024)
Cardiovascular disease (CVD) is the principal cause of death globally, yet there is a noticeable gap in literature regarding the knowledge of nursing students about this critical health issue. This study aimed to assess the understanding of CVD among students at a nursing college and to explore the association between their knowledge levels and socio-demographic characteristics. Employing a descriptive cross-sectional design, the research involved a random sample of 100 nursing students, using a standardized questionnaire validated by experts and tested for reliability (alpha correlation coefficient of 0.70). Statistical analysis was conducted using SPSS version 26, revealing that 59% of participants had a moderate level of knowledge about CVD. Based on these findings, we recommend the incorporation of more frequent educational sessions on cardiovascular health in nursing curricula to enhance student knowledge. Future research should expand on these findings to foster a deeper understanding of educational impacts on healthcare outcomes. Highlights: Moderate Knowledge: 59% of students have moderate CVD knowledge, indicating room for educational improvements. Reliable Assessment: The study used a validated questionnaire ensuring accurate knowledge assessment. Educational Recommendations: Suggests more frequent lectures to enhance student understanding of cardiovascular health. Keywords: Nursing Education, Student Awareness, Health Outcomes, Cardiovascular Disease, Knowledge